Adapting IntelliJ IDEA for Siemens’ OSGi Application Development - Biastinov, Vlad; Bruckner, Tomáš, 1974-; Banszel, Jiří; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
In large-scale enterprise software development, the Open Service Gateway initiative (OSGi) is widely used for building modular applications due to its ability to dynamically manage multiple modules. Siemens currently uses Eclipse as its primary Integrated Development Environment (IDE) for developing Polarion ALM, a Java-based OSGi application. Building Polarion ALM relies on Eclipse Tycho, which facilitates building OSGi projects within Eclipse but lacks support in IntelliJ IDEA. However, by 2024, IntelliJ IDEA has become the most popular Java IDE, preferred by 41% of developers compared to Eclipse's 23%. Providing developers with the choice of their preferred IDE — whether Eclipse or IntelliJ IDEA — is essential for enhancing the developer experience. This flexibility allows developers to work in the environment that best suits their individual preferences, boosting both satisfaction and productivity. The main goal of the thesis is to implement and validate a functional solution for IntelliJ IDEA that provides support for Eclipse Tycho. Additionally, both the backend and frontend will be tested to confirm they can be launched and debugged in IntelliJ IDEA. This process may require additional effort beyond the development of the solution itself. As the method, design science research is used, where the resulting artifact is a solution that enables Polarion ALM to be built and developed using IntelliJ IDEA, designed and implemented according to the requirements of the case organization. The result is a fully functional solution that enables a working development environment for Polarion ALM within IntelliJ IDEA. It includes a complete build process and ensures compatibility with existing project structures.
Vedoucí práce: Tomáš Bruckner
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: vývoj informačních systémů [obor dipl. práce]; diplomové práce; master's theses